PENERAPAN PROJECT BASED LEARNING (PJBL) BERBANTUAN KOMIK AUGMENTED REALITY MATERI SISTEM TATA SURYA DENGAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI - Lintang Kirana Leokiss Wijaya; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to design and implement ARLO (Augmented Reality Learning Optimized) Comic learning media as a means to enhance students' understanding of plant reproduction, in line with the Natural and Social Sciences (IPAS) curriculum at the elementary school level. A development research method was utilized with a descriptive qualitative approach. The findings indicate that the use of ARLO Comic can enhance students' interest and comprehension of the Solar System learning material. This learning media enables student interaction with learning content through Augmented Reality features, both in the classroom and at home. The study highlights the importance of developing learning media that aligns with students' learning needs, especially in improving learning outcomes on complex subjects. It is hoped that the use of ARLO Comic can complement conventional learning, assist teachers in explaining complex concepts visually and engagingly, and enhance students' abilities in critical thinking, collaboration, and communication.